IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG PROGRAM KELUARGA HARAPAN (PKH) OLEH DINAS SOSIAL DI KECAMATAN PANGALENGAN KABUPATEN BANDUNG - Rendy Adiwilaga; Widdy Yuspita Widiyaningrum; Dera Izhar Hasanah (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
The aim of PKH itself is to improve the standard of living of the community to be designated as KPM and to create a community mindset to be more independent and not dependent on others. The Family Hope Program (PKH) is a program of giving cash to Very Poor Households (RTSM) based on the terms and conditions that have been determined by carrying out its obligations as stated in the Regulation of the Minister of Social Affairs No.1 of 2018 concerning the Family Hope Program (PKH) tested based on the theory of implementation The policies of Edward III. The approach in this research uses qualitative research using natural backgrounds with the intention of interpreting the phenomena that occur and is carried out by involving various existing methods through interviews, observations, and use of documents. In this study, the PKH Facilitators must continue updating so that the community knows who is entitled to receive PKH assistance or who is entitled to receive KPM in accordance with the 7 (seven) criteria for KPM recipients with a Health Component (pregnant women and children aged 0 (zero) to 6 (six years), the Education Component (SD/ equivalent, SMP / equivalent and SMA / equivalent), and the Social Welfare Component (elderly 60 (sixty) years old and persons with disabilities), outside of these criteria are not are entitled to receive assistance from PKH.In addition, PKH Facilitators must have been certified through education and training within the Ministry of Social Affairs to carry out their duties so that the implementation of P2K2 activities, one of which is through the Financial Management and Business Planning modules by changing the mindset whether the money is for needs or wants.